Purvalanol A, olomoucine II and roscovitine inhibit ABCB1 transporter and synergistically potentiate cytotoxic effects of daunorubicin in vitro - Cihalova, Daniela; Hofman, Jakub; Ceckova, Martina; Staud, Frantisek (PloS one, 2013)
Cyclin-dependent kinase inhibitors (CDKi) have high potential applicability in anticancer therapy, but various aspects of their pharmacokinetics, especially their interactions with drug efflux transporters, have not yet been evaluated in detail. Thus, we investigated interactions of five CDKi (purvalanol A, olomoucine II, roscovitine, flavopiridol and SNS-032) with the ABCB1 transporter. Four of the compounds inhibited efflux of two ABCB1 substrates, Hoechst 33342 and daunorubicin, in MDCKII-ABCB1 cells: Olomoucine II most strongly, followed by roscovitine, purvalanol A, and flavopiridol. SNS-032 inhibited ABCB1-mediated efflux of Hoechst 33342 but not daunorubicin. In addition, purvalanol A, SNS-032 and flavopiridol lowered the stimulated ATPase activity in ABCB1 membrane preparations, while olomoucine II and roscovitine not only inhibited the stimulated ATPase but also significantly activated the basal ABCB1 ATPase, suggesting that these two CDKi are ABCB1 substrates. We further revealed that the strongest ABCB1 inhibitors (purvalanol A, olomoucine II and roscovitine) synergistically potentiate the antiproliferative effect of daunorubicin, a commonly used anticancer drug and ABCB1 substrate, in MDCKII-ABCB1 cells as well as in human carcinoma HCT-8 and HepG2 cells. We suggest that this pronounced synergism is at least partly caused by (i) CDKi-mediated inhibition of ABCB1 transporter leading to increased intracellular retention of daunorubicin and (ii) native cytotoxic activity of the CDKi. Our results indicate that co-administration of the tested CDKi with anticancer drugs that are ABCB1 substrates may allow significant dose reduction in the treatment of ABCB1-expressing tumors.
Keywords: roskovitin; Drug Synergism; Cell Proliferation; inhibitory proteinkinas; Adenosine Triphosphatases; cyklin-dependentní kinasy; Roscovitine; P-glykoproteiny; Protein Kinase Inhibitors; buněčné linie; Purines; ATP Binding Cassette Transporter, Subfamily B; antitumorózní látky; daunomycin; Cell Line; lidé; adenosintrifosfatasy; proliferace buněk; Antineoplastic Agents; Daunorubicin; Cyclin-Dependent Kinases; regulace genové exprese; Humans; Cell Membrane; puriny; buněčná membrána; Gene Expression Regulation; RNA, Messenger; synergismus léků; messenger RNA